The students' perceptions on the factors that motivate them to participate in accounting class / Ahmad Daud Marsam - Marsam, Ahmad Daud (2000)
This study presents and discusses the teaching methods that might contribute in motivating students to participate in accounting class. Extensive literature on different teaching methods had been reviewed. However, for the purpose of the study, only four teaching methods are considered: problem solving, question and answer session, feedback and group work. The objectives of the study are: to determine the students' perceptions towards the different teaching methods; to examine the perceptions of the male and female students; and to determine the perceptions of DIA students of Part 1, Part 3 and Part 6 on the various teaching methods. The study was conducted by distributing questionnaires to Diploma in Accountancy students at Universiti Teknologi MARA, Shah Alam. It is found that the students perceived as very important for the lecturer to explain in various techniques on area that they find difficulty to understand and to demonstrate the step in solving problem, which is consistent with previous study. However, the findings show that these students are reluctant to make comment in expressing their understanding on the topic taught which is inconsistent with the previous study. Further analysis conducted shows that there is no significant difference between gender and among students from different parts towards their perception on the teaching methods that motivate their class participation. This study provides an indication; it is not an ultimatum that the lecturer need to follow. Also, the study believes that the lecturer should put more focus on two way communication with the students and be more concern on the academic development of the students.